Mediações estéticas na formação docente: contribuições ao desenvolvimento do sujeito professor - Barreto, Ana Lucia de Oliveira (2018)
This research was made from the teacher training process, developed in a municipal school of Elementary School in the city of São Paulo. The research aimed to understand the meanings of educators on the constitutive role of aesthetic mediations and possible reverberations in their teaching practices. Anchored in a theoretical reference of Socio-historical Psychology (AGUIAR, 2006; AGUIAR et al, 2009; AGUIAR; BOCK, 2016), in Historical-Dialectical Materialism and in Historical-Critical Pedagogy (SAVIANI, 2003; 2004; 2008), I understand artistic production as a human objectification, in which the social being appropriates reality through shared reflective experiences and the senses , and art as an element that can enable subjects to critically understand reality, inciting transformative action. The objective of the training was to instigate teachers to review their teaching practices, from the perspective of humanization and awareness through art and ethical and political questions. The axis of the proposed training was to work directly with feeling, thinking, and acting in the school context, acting creatively, asking about the senses of what they do and what they see experiencing aesthetic learning situations. In order to produce the data we used, as a methodological instrument, questionnaires and the collective planning of a school activity, in addition the records of the discussions of the training groups were considered. The analysis and interpretation of the data were inspired by the Nucleus of Significance procedure (AGUIAR; OZELLA, 2006; 2013; AGUIAR; SOARES; MACHADO, 2015), seeking an interpretative analysis of the meanings produced by the participants. This course indicated that the teacher, when provoked by the reflection, starts to review his professional action and his own existence. Aesthetic mediations, in the perspective of breaking patterns of behavior, teaching, learning and curricular content, foster gaps and impel amplifications of thoughts, ways of seeing and feeling art, as well as being and being in the world. By questioning conceptions and choices, aesthetics articulates with ethical and political positioning, preserves and announces democratic values. The aesthetic dimension invigorates the educator in relation to learning to listen, to see, to be, to care and to have affection, and this unfolds in the production of knowledge, provoking the rethinking of exclusionary, discriminatory and alienating school practices